First report of the characterization of the pathophysiological mechanisms caused by the freshwater catfish Pimelodus maculatus (order: Siluriformes) - Sarmiento, Beatriz Elena; Rangel, Marisa; Goncalves, Jacqueline Coimbra; Pereira, Lilibete; Rego, Solange; Campos, Leandro Ambrosio; Haddad, Vidal [UNESP]; Mortari, Marcia Renata; Schwartz, Elisabeth F. (Elsevier B.V., 2015)
Injuries caused by aquatic animals in Brazil in most cases are provoked by marine and freshwater catfish. Pimelodus maculatus is a freshwater catfish very common in Brazilian basins that causes frequent accidents mainly amongst fishermen, and whose venom characteristics and pathological mechanisms of the venom are poorly known. In the present study for the first time, we have characterized the main pathophysiological mechanisms associated with the clinical manifestation (pain, local inflammation and edema) of the envenomations caused by P. maculatus crude venom. It was estimated that the crude venom of one P. maculatus stinger contains approximately 100 mu g of protein, likely the quantity involved in the envenomation. P. maculatus crude venom induced marked nociceptive and edematogenic effects and caused vascular permeability alterations at doses from 30 to 100 mu g/animal. Additionally, P. maculatus crude venom caused a decrease in the contraction force in in situ frog heart, did not cause hemorrhage or alterations in clotting times (prothrombin time and activated partial thromboplastin time), but induced significant changes in the levels of CK and its isoenzyme CK-MB in mice. In the present work, we present a correlation between the effects obtained experimentally and the main symptoms observed in the human accidents provoked by P. maculatus.
Keywords: Cardiotoxic activity; Edematogenic activity; Inflammatory activity; Catfish; Pimelodus maculatus; Venom